PENGARUH ORGANIZATIONAL TRUST, JOB SATISFACTION, DAN WELL-BEING TERHADAP WORK ENGAGEMENT PADA KARYAWAN OUTSOURCING - Alif Rafly Wahyudy; Tiara Puspa (EBID: Ekonomi Bisnis Digital, 2026)
This study analyzes the influence of organizational trust, job satisfaction, and well-being on work engagement among 200 outsourced employees in the Bogor City public service sector. The study used a quantitative approach with a survey method, while the data were analyzed using multiple linear regression. The results showed that organizational trust and well-being had a positive and significant effect on work engagement, while job satisfaction had a positive but insignificant effect. Well-being was the most dominant variable in increasing work engagement. The implications of this study emphasize the importance of public sector organizations building trust and improving the well-being of outsourced employees to maintain sustainable work engagement.